2010
DOI: 10.1002/dc.21598
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prescreen of cervical liquid‐based cytology preparations: Results of a study in an academic medical center

Abstract: A rapid prescreening or rapid rescreening method for quality assurance in cervical cytology has been used in Europe and in Canada but has not been accepted in the United States. The rapid prescreen method was tested in a cytology laboratory that serves an academic medical center with a high-risk population for cervical cancer. For a period of 3 months, a tray of 20 sequentially numbered Surepath™ liquid-based preparations, randomly selected from the cervical cytology daily workload, were each prescreened in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Other studies have also reported that the sensitivity tends to increase after the implementation of a rapid review as an IQC [19,24,25] . The rates of FNR detected by 100%-RR varied in different studies, i.e., between 1.07 and 33.1% [26][27][28][29][30][31] . What could account for the differences in sensitivity when applying the same technique?…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported that the sensitivity tends to increase after the implementation of a rapid review as an IQC [19,24,25] . The rates of FNR detected by 100%-RR varied in different studies, i.e., between 1.07 and 33.1% [26][27][28][29][30][31] . What could account for the differences in sensitivity when applying the same technique?…”
Section: Discussionmentioning
confidence: 99%
“…The widespread carbonate deposition of the Tamengo Formation is related to a transgression event also observed in the calcareous grainstones of the Tagatiya Guazu Formation (Itapucumi Group, Paraguay). This unit is thought to be a wave- and tide-dominated depositional environment that represents a shallow tidally-influenced setting on a rimmed carbonate ramp [ 16 ], where the association of Cloudina fossils with thrombolites together with remains of Corumbella [ 17 ] were found.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…In Corumbá, Cloudina occurred in a shallow, protected carbonate setting [ 16 ], whereas Corumbella lived in a calm terrigenous environment, indicated by its abundance in marls. In Paraguay, these animals probably co-occurred in environments with similar conditions of water temperature, depth, and salinity [ 17 ]. The siltstones and very fine-grained sandstones of the lower member of the Wood Canyon Formation in Nevada, USA, also bear Corumbella and Cloudina .…”
Section: Geological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations